Nutritional Content in Snack Food: Consumer Perceptions and Behaviors - Rosa Amalia; Dyah Ismoyowati; Guntarti Tatik Mulyati (APTA and DTIP FTP UGM, 2021)
People's lifestyles encouraged them to devour the main dish in a short amount of time. It demonstrated the value of snack foods as a source of supplementary energy. To present an example of marketing agro-industry in some healthy snack foods for college student, it was necessary to understand consumer behaviors regarding sugar intake in snacking. The marketers need to understand the customer perceptions and behaviors towards nutritional content in snack foods to create healthy snack food. The aims of this study were: 1) to analyze the consumer perceptions and behaviors of nutritional content in snack food products; 2) to identify dominant factors which affect the consumption of snack food products. The study was conducted on 200 respondents of college students. Snack foods were commonly consumed by college students, who were classified as adolescents, in between substantial meals. Descriptive statistics and Principal Component Analysis (PCA) were performed. Consumer impressions on a preliminary assessment of the nutrition label, which includes sugar components, were determined using descriptive statistics. Furthermore, PCA was performed to identify the main consumer characteristics that affect snacking, allowing the impact of sugar content on snack food consumption. The results indicated that the consumers were concerned enough about eating nutritious meals. Consumers, on the other hand, rarely read nutrition labels. The